Accumulated‐ and distributed‐reinforcer arrangements in the treatment of challenging mealtime behavior. (10th July 2022) - Chen, Elaine; Borrero, Carrie S. W.; Frank‐Crawford, Michelle A.; Borrero, John C.
Abstract: Treatment for inappropriate mealtime behavior often includes extinction and differential reinforcement of alternative behavior (DRA) in a distributed arrangement in which delivery of brief reinforcer access immediately follows each appropriate mealtime response. Alternatively, DRA may be arranged using accumulated reinforcement wherein delivery of longer, continuous access to reinforcers follows the consumption of multiple consecutive bites. Research has suggested that individuals prefer and perform better under accumulated arrangements in academic settings; however, no research to date has evaluated the efficacy of accumulated arrangements with children with feeding disorders. We compared preference for and efficacy of distributed and accumulated (with and without tokens) reinforcement with nonremoval of the spoon. All three treatments effectively reduced inappropriate mealtime behavior and increased acceptance for two participants and decreased packing and increased mouth clean for one participant. Two participants preferred distributed reinforcement and one preferred accumulated reinforcement without tokens. Findings differ from some previous research, which demonstrated that participants favored accumulated arrangements in academic contexts.